Addams Family values - Huston, Anjelica; Julia, Raul.; Lloyd, Christopher, 1938-; Cusack, Joan, 1962-; Ricci, Christina; Kane, Carol, 1952-; Sonnenfeld, Barry; Rudnick, Paul.; Addams, Charles, 1912-1988.; Paramount Pictures Corporation (Hollywood, Calif. : Paramount Pictures, 1999)
It's love at first fright when Gomez and Morticia welcome a new addition to the Addams household: Pubert, their soft, cuddly, mustachioed baby boy. As Fester falls hard for voluptuous nanny Debbie Jilnsky, Wednesday and Pugsley discover she's a black-widow murderess who plans to add Fester to her collection of dead husbands. The family's future grows even bleaker when the no-good nanny marries Fester and has the kids shipped off to summer camp. But Wednesday still has a Thing or two up her sleeve.
Based on characters created by Charles Addams.
Originally produced as a motion picture in 1993.
Special features: Trailers.
Editors, Arthur Schmidt, Jim Miller ; music, Marc Shaiman.
Anjelica Huston, Raul Julia, Christopher Lloyd, Joan Cusack, Christina Ricci, Carol Kane.
MPAA rating: PG-13.
Keywords: Addams family (Fictitious characters) -- Drama; Infants -- Drama; Nannies -- Drama; Feature films; Comedy films; DVDs for the hearing impaired